Kebijakan Nota Kesepahaman Pengawasan Partisipatif BAWASLU dan JPS Sumatera Barat pada Pemilihan Umum Tahun 2024 - Al Habsy, M Hafiz; Putri, Nora Eka (YASIN, 2025)
The General Election Supervisory Agency (BAWASLU) has several limitations in achieving electoral justice technically, namely personnel limitations and the vast geographical scope of the supervisory area. Then the challenge becomes even more complicated in the simultaneous 2024 elections, which place digital media as the primary space for political campaigns. Also, in the policy of the Memorandum of Understanding for participatory oversight with the West Sumatra Editors' Network (JPS), 10 out of 16 JPS media outlets placed political advertisements on their respective websites or news portals, indicating that the media have political tendencies. The goal of this research is to examine the implementation of the policy and the news coverage it generates. The research method used is quasi-qualitative with a policy analysis framework. Data collection was conducted through observation, interviews, and document studies with key informants from BAWASLU West Sumatra and JPS. In addition, this research is supported by the framing analysis method to see how the news in participatory oversight policies is framed and constructed to encourage active public participation in election oversight. The results of this study show the role of each institution, with BAWASLU West Sumatra playing the role of agenda-setting in news coverage by determining and providing information, while JPS constructs and publishes the news. Then, the results of the framing analysis show that the JPS media predominantly uses event frames (43%) and idea frames (43%), while the low figurative frame (14%) indicates the media's independence from political interests. However, the tone or mood of the news coverage is dominated by a hopeful tone (73.5%) compared to an advisory tone (21.8%), thus tending to build optimism rather than encouraging direct public participation. In general, this news pattern directs JPS more towards the public relations function of BAWASLU rather than the educational function to encourage active public participation in election supervision.